Transcriptomic landscape of breast cancers through mRNA sequencing - Eswaran, Jeyanthy; Cyanam, Dinesh; Mudvari, Prakriti; Reddy, Sirigiri Divijendra Natha; Pakala, Suresh B.; Nair, Sujit S.; Florea, Liliana; Fuqua, Suzanne A. W.; Godbole, Sucheta; Kumar, Rakesh (Scientific reports, 2012)
Breast cancer is a heterogeneous disease with a poorly defined genetic landscape, which poses a major challenge in diagnosis and treatment. By massively parallel mRNA sequencing, we obtained 1.2 billion reads from 17 individual human tissues belonging to TNBC, Non-TNBC and HER2-positive breast cancers and defined their comprehensive digital transcriptome for the first time. Surprisingly, we identified a high number of novel and unannotated transcripts, revealing the global breast cancer transcriptomic adaptations. Comparative transcriptomic analyses elucidated differentially expressed transcripts between the three breast cancer groups, identifying several new modulators of breast cancer. Our study also identified common transcriptional regulatory elements, such as highly abundant primary transcripts, including osteonectin, RACK1, calnexin, calreticulin, FTL and B2M and “genomic hotspots” enriched in primary transcripts between the three groups. Thus, our study opens previously unexplored niches that could enable a better understanding of the disease and the development of potential intervention strategies.